The impact of baby care education provided to mothers in the early postpartum period on the maternal role and postpartum anxiety - Özkoç, Melike; Tandoğan, Özden (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Baby care training given to mothers can help them feel more secure and make their motherhood role more effective. The aim was to determine the effect of early postnatal infant care training on the maternal role and anxiety in first-time mothers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study involved 60 mothers of which n=30 were in a control group with treatment as usual and n=30 were in the intervention group receiving special training on infant feeding, basic hygiene practices, baby’s sleep patterns and basic care skills. Training took place in the first 8 and 24 hours after birth and mothers were followed up 5 weeks later. The “Barkin Maternal Function Inventory (BMFI)” and “Postpartum Anxiety Scale (PAS)” were used to measure maternal roles and postpartum anxiety at 6 weeks after birth. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Participants were usually between 28–32 years of age and were first-time mothers. Six weeks after birth, there was a statistically significant difference in BMFI total scores between the experimental and control groups (p<0.001), while the experimental group scored higher (89.8±11.01). There was no significant difference between the groups in terms of postpartum anxiety. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Significant improvements were observed in the anxiety levels and mothering skills of mothers who received training. It is recommended that similar training programs be implemented on a larger scale and their effects be monitored long-term.